Early Childhood Caries-related Visits to Hospitals for Ambulatory Surgery in New York State - Sangeeta Wadhawan, BDS, MPH; Jayanth V. Kumar, DDS, MPH; Victor M. Badner, DMD, MPH; (Blackwell Synergy, 2003)
The objective of this study was to assess the utilization of ambulatory surgery at hospitals for the treatment of early childhood caries in New York State